The development of secured consolidated information resource of activity analysis of the poultry industry in ukraine - Azarova, Anzhelika; Shiyan, Anatoliy; Mironova, Yulia; Shturma, Liudmyla (Technology audit and production reserves, 2019)
The object of research is the process of consolidating business information. The paper considers the creation and use of a powerful component of the business analytics system – a consolidated information resource that improves the understanding of the business process, analyzes activities and improves the process of managerial decision-making in the poultry market of Ukraine. Methods and tools that are used in the process of building an information resource are substantiated. In particular, analysis and comparison methods are used to select a database management system, data warehouse model, and programming language. Also in the research process, a synthesis method is used to substantiate the requirements for the subject of study and a modeling method to create an ER model. As well as methods of induction and deduction – to form conclusions and a method of expert evaluation – to determine the economic feasibility of developing a consolidated information resource. A goal tree is formed to create a consolidated information resource. An entity-relationship diagram is developed. And to systematize the information received and analyze it in detail, a database is designed. This process is implemented using DBMS (database management system) MS SQL and JavaScript. It is used as a means of accumulating data and a tool for analyzing the activities of both a single producer in the poultry market and the entire poultry industry together. Based on the results of the study, it is possible to prove the economic and functional feasibility of introducing and using a consolidated information resource. Since the proposed development significantly increases the level of leadership awareness of the performance indicators of both individual enterprises and the industry as a whole, for making high-quality and informed management decisions. The introduction and use of a secure consolidated information resource significantly reduces the time to receive and process the necessary information and makes this process safe. In addition, this consolidated information resource has a high level of commercial potential and opportunities for further improvement, taking into account the influence of the rapidly changing external and internal environment of its functioning.